The Role Of Nurul Islam Islamic Boarding School In The Development Of Education In Ogan Ilir Regency In 1932-1980 (Contribution Of History Learning Materials In Grade XI Of Al-Anwar Foundation Seribandung Senior High School) - Nelly Syaparingga; Syafruddin Yusuf; Hudaidah Hudaidah (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This research was conducted at Nurul Islamic Boarding School in Seribandung Village, Tanjung Batu District, Ogan Ilir District. The formulation of the problem is (1) how the development of Nurul Islam Islamic boarding schools (2) how the role of Islamic boarding schools in the development of education in Ogan Ilir, (3) how the pattern of education applied by pesantren in the development of education in Ogan Ilir and (4) how the pesantren impacts on development education at Ogan Ilir. This study uses historical methods. The research steps are heuristics, source criticism, interpretation, and historiography. The results of the study were the role of the Nurul Islam Seribandung Islamic boarding school in the education sector in Ogan Ilir and South Sumatra districts. This pesantren provides Islamic-based education to children without having to go out of town. The santri are equipped with social sciences such as jannies, lectures, marhaban, which are methods of developing da'wah in the Ogan Ilir community. The Islamic Boarding School Nurul Islam experienced a peak in 1970 to 1980 with a number of 2,678 santri to 1,236 santri. Nurul Islam boarding school has succeeded in completing santri with sufficient religious knowledge. The alumni succeeded in establishing Islamic boarding schools in their area and became great scholars. Changes in people's lives follow the pattern applied by Nurul Islamic boarding schools, ranging from changes in morals, life, and awareness to charity.